When phylogenetics met biogeography: Willi Hennig, Lars Brundin and the roots of phylogenetic and cladistic biogeography. (19th October 2022) - Morrone, Juan J.
Abstract: Willi Hennig's (Beitr. Ent. 1960, 10, 15) Die Dipteren‐Fauna von Neuseeland als systematisches und tiergeographisches Problem applied a phylogenetic approach to examine the distributional patterns exhibited by the Diptera of New Zealand. Hennig showed how phylogenetic trees may be used to infer dispersal, based on the progression and deviation rules, and also discussed the existence of vicariance patterns. The most important author who applied Hennig's phylogenetic biogeography was Lars Brundin, when analysing the phylogenetic relationships of two taxa of Chironomidae (Diptera) and using them to examine the biogeographic relationships of Australia, New Zealand, South America and South Africa. The relevance of Brundin's contribution was noted by several authors, as it began the cladistic or vicariance approach to biogeography, that implies the discovery of vicariance events shared by different monophyletic groups. Both phylogenetic and cladistic biogeography have a place in contemporary biogeography, the former for analysing taxon biogeography and the latter when addressing Earth or biota biogeography. The recent use of the term "phylogenetic biogeography" to refer to a posteriori methods of cladistic biogeography is erroneous and should be avoided.